2016
DOI: 10.1590/0037-8682-0165-2016
|View full text |Cite
|
Sign up to set email alerts
|

Benznidazole therapy for Chagas disease in asymptomatic Trypanosoma cruzi -seropositive former blood donors: evaluation of the efficacy of different treatment regimens

Abstract: Introduction: Chagas disease currently affects 5.7 million people in Latin America and is emerging in non-endemic countries. There is no consensus concerning the effi cacy of trypanocidal therapy for patients with the chronic form of the disease. We evaluated cardiac function and sociodemographic, clinical, and serologic characteristics of a group of asymptomatic Trypanosoma cruzi-seropositive former blood donors, and compared the effects of benznidazole treatment applied for different lengths of time. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…5 Drug treatments are effective during the acute phase of the infection as well as in children, but efficacy appears questionable for patients in the chronic phase, with a very high variability in treatment outcomes. [6][7][8][9][10] Thus, complementary or alternative tools are urgently needed for a better care of infected patients, and vaccines may represent an attractive strategy for the treatment, prevention, or control of T. cruzi infections.…”
Section: Introductionmentioning
confidence: 99%
“…5 Drug treatments are effective during the acute phase of the infection as well as in children, but efficacy appears questionable for patients in the chronic phase, with a very high variability in treatment outcomes. [6][7][8][9][10] Thus, complementary or alternative tools are urgently needed for a better care of infected patients, and vaccines may represent an attractive strategy for the treatment, prevention, or control of T. cruzi infections.…”
Section: Introductionmentioning
confidence: 99%
“…Of the included studies, 43.5% (n = 10) had a sample size smaller than or equal to 50 individuals 6,[11][12][13][14][15][16][17][18][19] and 56.5% (n = 13) greater than 50 individuals [20][21][22][23][24][25][26][27][28][29][30][31][32] . Five articles (21.7%) [11][12][13]19,21 had a higher risk of methodological bias, with scores lower than 15 in the quality assessment according to Downs and Black 10 , who claimed that the factors related to the potential confounders are the most affected.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, cases of seronegativation were observed in 80% (n = 8) of the studies evaluating this parameter, being observed from 4.6 to 73.0% of participants with negative serology after benznidazole use 12,13,17,23,24,[30][31][32] . In 60.9% (n = 14) of the studies, adverse effects were reported, such as: gastrointestinal symptoms, dermatitis, cutaneous reactions, among others 6,11,14,15,17,18,20,22,23,[25][26][27][28]30 (Table 2). Vallejo et al 33 5 mg/kg twice daily/ 60 days 100.0 ---Maculopapular rash, facial rash, fever, rash.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations